Pelatihan Dan Pendampingan Pemasaran Digital Pada UMKM Kebab Nusantara Makassar - Rusmiati Rusdam; Valentino Aris; Airul Syahrif; Sri Asmirani; Adawiyah Asti Khalil (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
This Community Service Program (PKM) aims to enhance the digital marketing capacity of the micro, small, and medium enterprise (SMEs) Kebab Nusantara Makassar through a series of structured training and mentoring activities. The program was initiated in response to the low level of digital literacy among culinary entrepreneurs, which limits their promotional reach and competitiveness in the digital era. The method employed was a participatory action approach consisting of needs analysis, socialization, training, and mentoring in content creation, content planner development, and content distribution via social media, particularly Instagram. The program was conducted over three months, from June to September 2025, involving the owner and staff of the MSME as active participants. The results indicate a significant improvement in key digital marketing indicators: impressions increased by 424.8%, reach by 91%, interactions by 1,476%, profile visits by 254%, and follower growth by 56%. Furthermore, the partner demonstrated independence in managing their social media account by continuing to produce and publish content after the program ended. Therefore, this PKM program proved effective in improving digital literacy, strengthening social media marketing skills, and expanding market reach. The implementation of continuous training and mentoring is recommended as a replicable model for building digital capacity among MSMEs in the culinary sector.